Constructing Scholarly Identity and Agency through Modality and Lexical Choice in Undergraduate Writing - Mubarak, Zia Hisni; Tewarat, Sipri Hanus; Afriana, Afriana (Asosiasi Ide Bahasa Kepri, 2025)
This study investigates how undergraduate students construct scholarly identity and express agency in academic writing through the use of modality and lexical choices. Drawing on a discourse analysis framework, the research analyzes a corpus of undergraduate essays from an English language education program, focusing on the strategic deployment of modal verbs, adverbs, evaluative language, and hedging devices. The analysis reveals that students vary in their ability to position themselves authoritatively in the academic discourse community. High-achieving students tend to use modality to balance assertion and caution, displaying nuanced control over epistemic stance and interpersonal engagement. In contrast, lower-achieving students often rely on assertive or vague expressions that limit dialogic interaction with potential readers. Additionally, lexical choices such as abstract nouns, nominalizations, and evaluative adjectives are found to be instrumental in shaping a credible scholarly persona. These findings underscore the importance of explicit instruction in linguistic features that construct academic voice and identity. The study contributes to the growing body of research on student writing by highlighting the role of language in mediating both personal agency and disciplinary alignment in academic discourse.